Social Solidarity of The Wadiabero-Haiya People Diaspora - Alwi, Alimin; Ram, St. Wijdanah; Dinda, La Ode (CV. Literasi Indonesia, 2024)
The problem with migrant communities is that they often only show the phenomenon of earning a living for their families. It is not uncommon for migrant communities to live in one area and not show solidarity behavior, especially in their hometown. In contrast to the Wadiabero-Haiya migrants who show solidarity behavior for their hometown, namely in Wadiabero Village, Gu District, Central Buton Regency. The research uses descriptive qualitative methods, data obtained through participant observation, in-depth interviews, and documentation studies. The results of this research show that: (1) the Wadiabero-Haiya diaspora is spread across the archipelago and neighboring countries; In the archipelago, it is distributed on Papua Island, Maluku Island and its surroundings, on Sulawesi Island, Java Island, Kalimantan Island and Sumatra Island. In neighboring countries, spread across Sabah and Sarawak (2) ways to increase the solidarity of the Wadiabero-Haiya Diaspora Community, namely religious education, introduction to culture and social values, and example; (3) a form of social solidarity, namely mechanical solidarity in the form of a shared view to advance one's hometown, and organic solidarity in the form of mutual need between migrants from different areas for one's hometown. The solidarity created in Wadiabero Village is visible in religious activities, arts activities, and sports activities.